Case Report: Early detection of pancreatic pre-cancer lesion in multimodal approach with exosome liquid biopsy - Dhani, Harmeet; Hinestrosa, Juan Pablo; Izaguirre-Carbonell, Jesus; Balcer, Heath I.; Kurzrock, Razelle; Billings, Paul R. (Frontiers in Oncology, 2023)
Background The detection of pancreatic ductal adenocarcinoma (PDAC) lesions at pre-cancerous or early-stages is critical to improving patient survival. We have developed a liquid biopsy test (ExoVita®) based on the measurement of protein biomarkers in cancer-derived exosomes. The high sensitivity and specificity of the test for early-stage PDAC has the potential to improve a patient’s diagnostic journey in hopes to impact patient outcomes. Methods Exosome isolation was performed using alternating current electric (ACE) field applied to the patient plasma sample. Following a wash to eliminate unbound particles, the exosomes were eluted from the cartridge. A downstream multiplex immunoassay was performed to measure proteins of interest on the exosomes, and a proprietary algorithm provided a score for probability of PDAC. Results We describe the case of a 60-year-old healthy non-Hispanic white male with acute pancreatitis who underwent numerous invasive diagnostic procedures that failed to detect radiographic evidence of pancreatic lesions. Following the results of our exosome-based liquid biopsy test showing "High Likelihood of PDAC", in addition to KRAS and TP53 mutations, the patient decided to undergo a robotic pancreaticoduodenectomy (Whipple) procedure. Surgical pathology confirmed the diagnosis of high-grade intraductal papillary mucinous neoplasm (IPMN), which was consistent with the results of our ExoVita® test. The patient’s post-operative course was unremarkable. At five-month follow-up, the patient continued to recover well without complications, in addition to a repeat ExoVita test which demonstrated “Low Likelihood of PDAC”. Conclusion This case report highlights how a novel liquid biopsy diagnostic test based on the detection of exosome protein biomarkers allowed early diagnosis of a high-grade precancerous lesion for PDAC and improved patient outcome.